1, 1′-butylenebis(3-methyl-3H-imidazol-1-ium) Hydrogen Sulfate Catalyzed One-Pot Multi-Component Synthesis of Unsymmetrical Polyhydroquinoline Derivatives. (7th August 2016) - Khaligh, Nader Ghaffari
Abstract : 1, 1′-butylenebis(3-methyl-3H-imidazol-1-ium) hydrogen sulfate as an efficient, halogen-free, and reusable binuclear Brönsted ionic liquid catalyzed the synthesis of ethyl-4-aryl/heteryl-hexahydro-trimehtyl-5-oxoquinoline-3-carboxylates by the one-pot condensation of dimedone, aryl/heteryl aldehydes, ethyl acetoacetate, and ammonium acetate under solvent-free conditions. This method has the advantages of high yields, clean reaction, simple methodology, and short reaction time. The ionic liquid could be recycled and reused four times without significant loss of in the catalytic activity.